Identification of Black Soldier Fly (Hermetia illucens) Maggot Growth Using Different Growth Media - Ulaan, Magdalin; Indriani, Yeni (Jurnal Biologi Tropis, 2024)
One alternative feed that meets the requirements as a source of protein is the larvae of the black soldier fly (Hermetia illucens or called maggot). Maggot Black Soldier Fly (BSF) is the larva of a type of black soldier fly that is able to process various types of organic waste quickly, easily reproduce, and has a high protein of 61.42%.The purpose of this study was to determine which type of growth media is suitable for optimal maggot growth. This study used a complete randomized design (CRD) with 3 treatments and three replications. The treatments in this study were Media A (Tofu pulp + 5 ml EM4 + 500 ml), Media B (Coconut pulp + 5 ml EM4 + 500 ml), Media C (Fine rice bran + 5 ml EM4 + 500 ml). Data were analyzed using analysis of variance (ANOVA) with a real level of 0.05. The results showed that growing media with media treatment C (Fine rice bran + 5 ml EM4 + 500 ml) gave significant results (P <0.05) on maggot weight with an average value of 29.3 grams and the highest maggot length growth with an average value of 1.7 cm during 14 days of maintenance. Thus, different growing media have a significant effect on the growth of Black Soldier Fly Maggot (Hermetia illucens).